Tophaceous gout in the sternoclavicular joint. Issue 10 (14th October 2020) - Sahdev, Nikhil; Smelt, Jeremy; Avila, Zoe; Tennent, Duncan; Hunt, Ian
Abstract: Gouty arthritis commonly occurs in peripheral synovial joints and involvement in the thoracic cage is extremely rare. We report a case of a 52-year-old presenting with a painful bony mass in her sternal notch. Imaging demonstrated a lobulated calcified and necrotic lesion causing mass effect on adjacent structures. Excision biopsy confirmed a benign cystic lesion with amorphous material containing needle-shaped refractile crystals suggestive of uric acid. Tophaceous gout was diagnosed. Presence of a periarticular mass with characteristics of gout should warrant investigation with biopsy and imaging. This can prevent misdiagnosis of malignancy and avoid unnecessary surgery in asymptomatic lesions.